Uporaba spletnih modelskih napovedi za napovedovanje vetra pri jadranju na deski in kajtanju - Majerič, Matej (Šport (Ljubljana), 2018)
The aim of this paper was to present the use of Web Model Forecasts for forecasting the wind condiotions for windsurfing and kiteboarding in Slovenia and its surroundings. Various meteorological models are used for wind forecasts. These are mathematical equations that numerically describe the current weather conditions in the atmosphere and simulate the development of future weather phenomena. The best known are the European Centre for Medium- Range Weather Forecasts (ECMWF) and United States National Centers for Environmental Prediction (NCEP). The available model predictions use and combine various web applications (eg. Windguru, Windfinder, Windy, etc.), which prepare (for short and long term) forecasts of speed and direction of the wind, temperature, cloudiness, precipitation, wave heights, etc. In Slovenia and its surrounding, there are more than 35 windsurfing and kiteboarding spots in a radius of aprok. 200 km from Ljubljana. With the help of web modeling forecasts, a reliable wind can be predicted for a certain area and spots. The method of using different mathematical models (NEMS, GFS, WRF ...) in predicting the wind is presented in this paper on the example. We found out, that we should logically combine different web applications. In doing so, we can get the experience on which we can even more reliably forecast the wind. Beside that it is always good to take into account local specificities and the opinions of experienced meteorologist.
Keywords: jadranje na deski; kajtanje; meteorološki modeli; spletne modelske napovedi; vetrovi (meteorologija); vodni športi